Drug Repurposing of Anticancer Agents JP-8g and REDX05358 Against the Target Protein Plectin 1a in Epidemolysis Bullosa Simplex with Muscular Dystrophy (EBS-MD) - Fathima Abbas (International Journal of Cell Biology and Cellular Functions, 2025)
Epidermolysis Bullosa Simplex with Muscle Dystrophy is a genetic disease affecting the skin and muscles which can be seen at birth or start at adulthood due to the mutation in the protein Plectin 1a (PLEC gene) causing skin blisters and muscle weakness. This protein is seen in sarcolemma, Z disks in skeletal muscles, hemidesmosomes in skin and cardiac muscles giving stability to cytoskeleton, playing a crucial role in neuromuscular transmission but when get mutated it leads to lack of cytoskeleton support in connecting the intermediate filaments to microtubules, myosin and actin filaments. This research aims at treating this disease with two anticancer agents against the mutated plectin1a. Different bioinformatics tools are used to get the effectiveness of the two anticancer agents against the therapeutic target protein. Molecular docking between the drugs and target in PyRx screening software and further visualization of those interactions in BIOVIA Discovery Studio are done. SwissADME tool evaluated the pharmacological properties of the drugs. Three ligand molecules JP-8g, REDX05358 and CAY10736 were selected for molecular docking with high negative binding affinity (least binding affinity) and pharmacological properties of two were studied. Anticancer agents JP-8g and REDX05358 are finally selected for drug repurposing against the mutated plectin 1a in EBS-MD as they give good molecular docking score and good ADME properties
Keywords: ADME; BIOVIA; Epidermolysis Bullosa Simplex with Muscular Dystrophy (EBS-MD); JP-8g; PyRx; REDX05358; ligands; molecular docking; plectin 1a acting binding domain